Geographic distribution of the incidence of colorectal cancer in Iran: a population-based study - Khosravi Shadmani, Fatemeh (Epidemiol Health, 2017)
OBJECTIVES: Colorectal cancer (CRC) is the third most common cancer and the fourth most common cause of cancer death in the world. The aim of this study was to investigate the provincial distribution of the incidence of CRC across Iran. METHODS: This epidemiologic study used data from the National Cancer Registry of Iran and the Center for Disease Control and Prevention of the Ministry of Health and Medical Education of Iran. The average annual age-standardized rate (ASR) for the incidence of CRC was calculated for each province. RESULTS: We found that adenocarcinoma (not otherwise specified) was the most common histological subtype of CRC in males and females, accounting for 81.91 and 81.95% of CRC cases, respectively. Signet ring cell carcinoma was the least prevalent subtype of CRC in males and females and accounted for 1.5 and 0.94% of CRC cases, respectively. In patients aged 45 years or older, there was a steady upward trend in the incidence of CRC, and the highest ASR of CRC incidence among both males and females was in the age group of 80-84 years, with an ASR of 144.69 per 100,000 person-years for males and 119.18 per 100,000 person-years for females. The highest incidence rates of CRC in Iran were found in the central, northern, and western provinces. Provinces in the southeast of Iran had the lowest incidence rates of CRC. CONCLUSIONS: Wide geographical variation was found in the incidence of CRC across the 31 provinces of Iran. These variations must be considered for prevention and control programs for CRC, as well as for resource allocation purposes.